The peptide genomic therapy increases antibacterial immunity and survival in sepsis by reprograming the gene orthologs of human immunodeficiencies in the spleen and lungs - Qiao, Huan; Zienkiewicz, Jozef; Liu, Yan; Hawiger, Jacek (Frontiers in Immunology, 2025)
Sepsis is a life-threatening complication of infections afflicting 49 million patients worldwide with 11 million sepsis-related deaths. In the USA, this growing public health problem concerns 1.7 million adult and pediatric patients. An estimated 1 million patients with asplenia or hyposplenia are particularly vulnerable to sepsis. We show that the Peptide Genomic Therapy (PGT) with the cell-penetrating Nuclear Transport Checkpoint Inhibitor (NTCI) peptide increased 29 times bacterial clearance in the spleen, a major blood-filtering immune organ in the preclinical model of sepsis, when combined with the antibiotic. Likewise, the PGT with NTCI peptide increased antibacterial immunity in the lungs, the frequent site of bacterial infections in spleen-compromised hosts. The survival reached 80% when the NTCI peptide was added to antibiotic, compared to 44% with meropenem alone. The NTCI peptide reprogrammed the expression of the gene orthologs responsible for human immunodeficiencies, also referred to as the Inborn Errors of Immunity (IEI). The 227 IEI genes were reprogrammed in the spleen and 215 in the lungs, while the mediators of inflammation in blood (IL-6, IL-10, TNFα, Interferon γ, and MCP1) were normalized by the NTCI peptide. Thus, the PGT with NTCI peptide combined with antibiotic significantly increased the antibacterial immunity in the spleen and lungs and almost doubled survival in sepsis.